Measurement of Competitiveness of Nature-Based Tourist Destinations: application to National Parks in Brazil - DOS ANJOS, Francisco Antonio; DA ROSA, Sabrina (Journal of Environmental Management and Tourism; Vol 12 No 5 (2021): JEMT Volume XII Issue 5(53) Fall 2021DO - 10.14505//jemt.v12.5(53).05, 2021)
The theme of the competitiveness of tourist destinations is broad and complex, and so are the various evaluation models being tested for various destination typologies. Understanding destination competitiveness leads to the ability to increase tourism revenue, attract more visitors, and provide satisfying and memorable experiences. This study aims to evaluate the factors of Competitiveness of Nature-Based Tourist Destinations, from the perspective of demand. The matrix of attributes was submitted to 637 visitors from the 74 Brazilian national parks, in January 2019, through an online form containing the 59 attributes validated by experts in the area and managers. Data collected from visitors were used to create a structural method. The analyses involved three steps: demographic descriptive analysis, exploratory factor analysis (EFA), confirmatory factor analysis (CFA) and multiple groups confirmatory factor analysis (MGCFA). The results confirmed 26 attributes, organized into five factors: Cultural Attractions, Infrastructure and Supporting Factors, Destination Management, Sustainability and Residents’ Quality of Life.